Patterns of Sexual Risk Behavior, HIV Infection, and Use of Health Services Among Sub-Saharan African Migrants in Portugal. Issue 7 (1st September 2020) - Dias, Sónia; Gama, Ana; Abrantes, Patrícia; Gomes, Isabel; Fonseca, Miguel; Reigado, Vera; Simões, Daniel; Carreiras, Emília; Mora, Cristina; Pinto Ferreira, Andreia; Akpogheneta, Onome; Martins, Maria O.
ABSTRACT: This study identified patterns of sexual risk behavior among a sub-Saharan African migrant (SAM) population in Portugal and examined its associations with human immunodeficiency virus (HIV) prevalence, sociodemographics, use of sexual health services, and HIV testing. A cross-sectional biobehavioral survey was conducted with a venue-based sample of 790 SAMs. Data were collected using questionnaires and rapid HIV tests. Cluster analysis identified five subgroups with differing levels of HIV infection (2.5% to 11.3%). In Cluster 1, most participants reported sexual abstinence over the past year and the remaining used condoms consistently; this cluster had the highest HIV prevalence (11.3%). In Cluster 2, most reported one sexual partner and all reported unprotected sex; all HIV-positive participants in this cluster were unaware of their HIV-positive status. In Clusters 3 and 4, most had four or more partners, yet all used condoms. In Cluster 3, 56.5% reported both regular and occasional partners. In Cluster 4, 74% had only occasional partners; all engaged in commercial sex. In Cluster 5, all reported four or more partners and condomless sex. In all subgroups we found low rates of HIV testing and high unawareness of HIV serostatus. Targeted prevention interventions are needed to reduce unprotected sexual relations and undiagnosed infection, as well as improve linkage to sexual health services.